PENATALAKSANAAN FISIOTERAPI PADA KASUS OSTEOARTHRITIS GENU BILLATERAL LATIHAN DI RSUD DR. MOEWARDI SURAKARTA - Nurfebriana, Riska Aditya; , Arif Pristianto, SSt.Ft, M.Fis (2017)
Background: osteoarthritis genu is a degenerative disease that attacks the cartilage, ligaments, and bones in the knee joint. Osteoarthritis is characterized by the deterioration of joint cartilage and accompanied by new bone formation and soft tissue around the joint. The main problem in such case is pain, limited range of motion, morning stiffness, and devormitas which causes changes in the pattern of gait. Physiotherapy modalities provided is Transcutaneus Electrical Nerve Stimulation (TENS) and exercise therapy. Aim of research: to find out the benefits of therapy with Transcutaneus Electrical Nerve Stimulation (TENS) and exercise therapy to reduce pain, increase range of motion, increase muscle strength and improve functional activities. Methods: The intervention provided consists of Transcutaneus Electrical Nerve Stimulation (TENS) for 15 minutes, and Therapeutic Exercise by doing functional movements of the knee joint of each movement performed 8 x 2 repetitions. Results: after treatment for 6 times the result a decrease in pain silent of knee dextra T1: 3 to T6: 1, tenderness T1: 4 to T6: 2 and painful motion T1: 5 to T6: 3, while the pain quietly knee sinistra T1: 3 became T6; 1, tenderness T1: 4 to T6: 2, and the pain of motion T1: 5 to T6: 2. To increase the range of motion active of dextra knee T1: S= 50-00-1000 becomes T6: S= 50-00-1100 , passive T1: S= 50-00-1050 becomes T6: S= 50-00-1150, on the knee sinistra active T1: S = 5o-00-1000 becomes T6: S= 50-00-1100 and on passive T1: S= 50-00-1050 becomes T6: S= 50-00-1150. Decrease in pain flexors of knee dextra T1: 4 to T6: 4.5 extensor T1: 4 to T6: 4.5 while the flexors of knee sinistra T1: 4 to T6: 4.5 extensor T1: 4 to T6: 4.5. Conclusion: Transcutaneus Electrical Nerve Stimulation (TENS) can reduce pain, in the case of exercise therapy can improve muscle strength, improve the LGS and the patient's functional ability.